Exploring Vocabulary Learning Strategies among Saudi EFL Learners through SMPs: A Mixed-Methods Study - Alharthi, Meshari (Forum for Linguistic Studies, 2025)
This study investigates Saudi English as a foreign Language (EFL) adult learners’ perceptions of vocabulary learning through social media platforms (SMPs) and explores which platforms and strategies they use. A sequential explanatory design was adopted, with data collected via questionnaires and interviews. Quantitative data were analyzed using SPSS, while interview data were examined through thematic analysis. The findings revealed a positive perception of the use of SMPs for vocabulary learning, with an average mean score of (M = 3.95, SD = 0.86). Popular SMPs included Instagram (76%) and WhatsApp (75%), followed by Snapchat (70%), YouTube (68%), Twitter (62%), Facebook (21%), and Google Plus (12%). Learners acquired vocabulary incidentally through SMPs, using them as research tools and employing strategies such as translation, interaction, and repetition, all of which feature in Schmitt’s taxonomy of vocabulary learning strategies. Additionally, students practiced new vocabulary through interaction with their environment, applying cognitive and metacognitive strategies, allowing them to learn at their own pace. Based on the results of this study, utilizing SMPs to enhance lifelong vocabulary learning and language acquisition among EFL learners is recommended. However, the generalizability of the results may be limited to the Saudi EFL adult learners living and studying in Saudi Arabia. Therefore, further research should be conducted to explore other contexts both inside and outside Saudi Arabia.